Study on Mechanical Failure and PermeabilityCharacteristicsof Porous Gas-Bearing Coal under Triaxial Stress - Xue-bo Zhang; Wen-yuan Wang; Ming Yang; Hang-hang Cai; Jia-jia Liu; Shuai-shuai Shen (Shock and Vibration)
To explore the mechanical failure and permeability characteristics of porous gas-bearing coal under triaxial stress, the triaxial compression experiment was carried out for porous and conventional gas-bearing coal samples based on the triaxial creep-seepage experiment system and sound emission signal acquisition system. Acoustic emission testing was carried out at the same time of loading failure. The experimental results showed that (1) under fixed gas pressure but changing confining pressure, the porous gas-bearing coal sample had higher peak strength and elastic modulus but lower peak strain; under changing gas pressure but fixed confining pressure, the porous gas-bearing coal sample had lower peak strength and peak strain but higher elastic modulus. When either confining pressure or gas pressure was changed, the mechanical properties of the two kinds of gas-bearing coal samples showed a good consistency, but the mechanical parameters differed greatly, with the peak strength, peak strain, and elastic modulus of porous coal samples are reduced by 1/4, 2/3, and 3/4, respectively. (2) When either the confining pressure or gas pressure was changed, the permeability of the porous gas-bearing coal sample was larger than that of the conventional gas-bearing coal sample. However, the change rules of permeability characteristics of the two were basically the same, except that there was a large difference in permeability value that the porous gas-bearing coal sample increases nearly twice as much as that of the conventional gas-bearing coal sample. (3) In the whole stress-strain process, the acoustic emission characteristics of the porous gas-bearing coal sample differed significantly from those of the conventional gas-bearing coal sample. The maximum ringdown count of the porous gas-bearing coal sample can be reduced by one-third at most, the maximum energy can be reduced by nearly half at most, and the maximum amplitude changes little with only 1–3 dB reduction. The research results have important guiding significance for the prediction of failure and instability of coal tunnel and the development of relevant protective techniques.